PENGGUNAAN VIDEO DARI MEDIA SOSIALPADA PELAJARAN SENI TARI SISWA KELAS VII’4 DI SMP NEGERI 2 PADANG - Putri, Willia; Sudarman, Yos (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2025)
This research aims to explain how teachers use videos from social media with lesson materials to enhance student understanding in the dance art subject for grade VII.4 at State Junior High School 2 Padang. This type of research is Classroom Action Research (CAR) conducted over 2 cycles with stages of planning, implementation, observation, and reflection. The research instruments used are written tests, observation notes, and interview notes. Data were collected through tests, observations, and interviews. The steps for data analysis include data association, data reduction, data presentation, data interpretation, and data conclusion. The results of the study indicate that the use of videos from social media with lesson materials to improve learning outcomes in dance art can enhance student understanding and make the learning activities more dynamic, as evidenced by the improved behaviour of the students. This will enhance student engagement and learning outcomes. The increase in student learning activities with certain metrics indicates this. The procedures intended for the cultural arts learning process using digital learning materials have been followed. Due to many students not taking their studies seriously, the implementation of learning in cycle I was not successful and is now in cycle II. Learning in cycle II has been well implemented, nearly all steps have been effectively carried out, and students are actively participating in learning, resulting in improved student learning outcomes. The improvement in students' written exam scores demonstrates how the use of video learning resources from social media has enhanced their learning outcomes. The average score in the written exam was 76% in cycle I and 88% in cycle II. Data analysis and discussion indicate that the use of edited videos from social media in dance instruction can improve students' learning results.